1988
DOI: 10.1007/bf01871743
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in tissues of fed and starved carp, acclimated to different temperatures

Abstract: The temperature dependence of the rates of protein synthesis in the red and white skeletal muscle of the carp (Cyprinus carpio) was measured using a method which involved a single injection of tritiated phenylalanine. Plasma and muscle-free phenylalanine quickly reached a plateau level at all temperatures. During the plateau phase the incorporation of label into protein was liner. Muscle from fish previously acclimated to either a low temperature (8°C) or a high temperature (28°C), showed marked differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1989
1989
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 27 publications
1
14
0
Order By: Relevance
“…1b and 1c). These results are in agreement with earlier studies that have shown that protein synthesis rates in fish increase with increasing water temperature when food is not limiting (Fauconneau and Arnal 1985;Loughna and Goldspink 1985;Watt et al 1988;Mathers et al 1993;McCarthy and Houlihan 1997) compared with no increase in synthesis rates when food is restricted (Foster et al 1992). In this study, between 5 and 14°C, a linear model was the best descriptor of the relationship between water temperature and protein synthesis in juvenile Atlantic wolffish (Figs.…”
Section: Figsupporting
confidence: 93%
“…1b and 1c). These results are in agreement with earlier studies that have shown that protein synthesis rates in fish increase with increasing water temperature when food is not limiting (Fauconneau and Arnal 1985;Loughna and Goldspink 1985;Watt et al 1988;Mathers et al 1993;McCarthy and Houlihan 1997) compared with no increase in synthesis rates when food is restricted (Foster et al 1992). In this study, between 5 and 14°C, a linear model was the best descriptor of the relationship between water temperature and protein synthesis in juvenile Atlantic wolffish (Figs.…”
Section: Figsupporting
confidence: 93%
“…A decline in the rates of protein synthesis with starvation has been described in a number offish species (Jackim and LaRoche 1973;Smith 1981;Haschemeyer 1983;Lied et al 1983;Pocrnjic et al 1983;Loughna and Goldspink 1984;Fauconneau et al 1986;Houlihan et al 1988b;Watt et al 1988). It has frequently been suggested that the reduction in oxygen consumption which accompanies starvation is partly due to a reduction in protein synthetic rates Smith 1981;Lied et al 1982).…”
Section: Starvationmentioning
confidence: 95%
“…It is notable that these values are similar to the QlO'S of around 2 for basal metabolism. To take one data set as an example of the kinds of results that have been obtained, measurements in carp have shown that muscle protein synthesis increases exponentially with temperature but that in fish acclimated at low temperatures (8°C) rates of synthesis are always higher than in fish acclimated to higher temperatures Watt et al 1988). A summary of the papers so far published on fish is given in Table 1.…”
Section: Exercisementioning
confidence: 98%
“…From these studies, it has been shown that changes in tissue protein metabolism occur when ration size is varied (Smith 1986;Houlihan et al 1988Houlihan et al , 1989, when food is withdrawn (Smith 1981;Pocrnjic et al 1983;Loughna and Goldspink 1984;Fauconneau 1985;Houlihan et al 1988;Watt et al 1988) and when fish are re-fed (Jackim and LaRoche 1973;Lied et al 1982;Houlihan 1988, 1989). However, in the first instance, effects of ration size on tissue protein metabolism have been studied over relatively long periods and in the second, effects of fasting have most often been measured several days after food withdrawal.…”
Section: Introductionmentioning
confidence: 99%